Resurgence : a Foreigner novel - Cherryh, C. J (Cherryh, C. J. Foreigner universe., 2020)
Bren Cameron, diplomat in residence, usually represents the ruler of the atevi state. But Ilisidi, the dowager, has been known to borrow his services from time to time<U+2014>and she has her own notions how to solve the simmering hostilities in the south of the atevi continent, playing one problem against another. This time, she is betting the hard-won northern peace<U+2014>and the lives of the people<U+2014>on being right. She has commandeered the Red Train, taken aboard what passengers she chooses, and headed for the snowy roof of the world, where a hard-scrabble town and its minor lord are the first pieces she intends to use.